Estimasi Biaya Pembangunan Rumah Instan Modul Adaptasi Ezygriya (RIMAE) Di Pandowoharjo Sleman DIY - SARI, SELY NOVITA (ReTII, 2021)
The house is one of the buildings that is used as a place to live as a basic need for shelter and rest. However, the fulfillment of these needs has not been fully owned by the community. Rumah Instan Modul Adaptasi Ezygriya (RIMAE) is a development of Rumah Instan Sederhana Sehat (RISHA). This innovation is carried out by developing fast-build technology using a knock-down system and has been provided in a manufacturing manner. This technology is not only very supportive of the acceleration of development, but also environmentally friendly when compared to conventional house construction. The purpose of this study is to discuss the cost comparison of a conventional house with Rumah Instan Modul Adaptasi Ezygriya (RIMAE). This research method is descriptive, namely direct interviewing of RIMAE applicators and direct observation in the field. The analytical method in this study is to calculate the volume of work, calculate the unit price coefficient, multiply the volume of work by the unit price coefficient, recapitulate the Budget Plan (RAB), and analyze the comparison of the total costs of the two buildings. Based on the analysis conducted, the cost needed to build Rumah Instan Modul Adaptasi Ezygriya (RIMAE) type-36 was Rp. 110,208,238.